2014
DOI: 10.1186/1471-2164-15-198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes involved in coronary artery calcification by transcriptome sequencing of cell lines

Abstract: BackgroundMassively-parallel cDNA sequencing (RNA-Seq) is a new technique that holds great promise for cardiovascular genomics. Here, we used RNA-Seq to study the transcriptomes of matched coronary artery disease cases and controls in the ClinSeq® study, using cell lines as tissue surrogates.ResultsLymphoblastoid cell lines (LCLs) from 16 cases and controls representing phenotypic extremes for coronary calcification were cultured and analyzed using RNA-Seq. All cell lines were then independently re-cultured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The models we developed in this study aimed at predicting the binary case-control statuses of age-matched Caucasian male patients. Hence, we first transformed the CAC scores (measured by Agatston method [ 47 ]) of the 32 Caucasian male subjects from the ClinSeq®; study that formed our discovery cohort (data previously published in [ 42 , 43 ]) into binary CAC states. 16 control subjects in this cohort had zero CAC scores corresponding to state “0", whereas the 16 age-matched cases had high CAC scores (ranging between 500 and 4400) corresponding to state “1".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The models we developed in this study aimed at predicting the binary case-control statuses of age-matched Caucasian male patients. Hence, we first transformed the CAC scores (measured by Agatston method [ 47 ]) of the 32 Caucasian male subjects from the ClinSeq®; study that formed our discovery cohort (data previously published in [ 42 , 43 ]) into binary CAC states. 16 control subjects in this cohort had zero CAC scores corresponding to state “0", whereas the 16 age-matched cases had high CAC scores (ranging between 500 and 4400) corresponding to state “1".…”
Section: Methodsmentioning
confidence: 99%
“…First, we leveraged a literature based strategy based on previous association studies of CAC to define a set of 57 single nucleotide polymorphisms (SNPs). As an alternative contextual approach, we utilized a standard feature selection and filtering approach in machine learning to identify 56 additional SNPs from the ClinSeq®; genotype data [ 42 , 43 ]. We assessed the predictive performances of these sets of SNPs with and without clinical variables in the ClinSeq®; cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The models we developed in this study aimed at predicting the binary case-control statuses of Caucasian male patients. Hence, we first transformed the CAC scores (measured by Agatston method (Agatston et al, 1990)) of the 32 Caucasian male subjects from the ClinSeq® study that formed our discovery cohort (data previously published in (Sen et al, 2014a, b)) into binary CAC states. 16 control subjects in this cohort had zero CAC scores corresponding to state “0”, whereas the 16 age-matching cases had high CAC scores (ranging between 500 and 4400) corresponding to state “1”.…”
Section: Methodsmentioning
confidence: 99%
“…Our study focused on Caucasian males due to higher coronary calcium scores observed among men compared to women (Raggi et al, 2008; Maas and Appelman, 2010), as well as higher prevalence of coronary calciumamong white Americans compared to black Americans (Lee et al, 2003). Using random forest modeling, which is a decision tree based machine learning method (Breiman, 2001) established as an effective tool for addressing the complexity of modelling with genomic data (Sun, 2009; Yang et al, 2010b; Dietterich, 2000), we first tested the collective ability of a set of SNPs derived from previous GWAS on CAC (SNP Set-1) in predicting advanced CAC with data from the ClinSeq® study (Biesecker et al, 2009) previously published in (Sen et al, 2014b,a). Upon deriving an alternative SNP set (SNP Set-2) and comparing its predictive ability to SNP Set-1 within the ClinSeq® discovery cohort with and without clinical data, we used data from the Framingham Heart Study (FHS) to test whether we could replicate the observed predictive patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless it is still unclear whether calcification affects particular matrix components in specific organs/tissues, whereas other areas remain unaffected and which molecules/pathways could be targeted for pharmacological approaches. To address these questions, investigations performed so far have looked at the specific expression/localization of already known proteins [2] or have used cell lines and tissue extracts to pick up unknown gene/proteins by means of “omic” techniques [3-5]. However, the major difficulty of these techniques is the ability to analyse a large number of proteins without losing the morphology and the tissue architecture and, even more importantly, to discriminate which proteins belong to normal or to pathologic areas.…”
Section: Introductionmentioning
confidence: 99%